2014
DOI: 10.1007/s12253-014-9833-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Heterogeneity of Glioblastoma and its Clinical Relevance

Abstract: Glioblastoma is the most common intracranial malignancy and constitutes about 50 % of all gliomas. Both inter-tumor and intra-tumor histological heterogeneity had been recognized by the early 1980-ies. Recent works using novel molecular platforms provided molecular definitions of these tumors. Based on comprehensive genomic sequence analyses, The Cancer Genome Atlas Research Network (TCGA) cataloged somatic mutations and recurrent copy number alterations in glioblastoma. Robust transcriptome and epigenome stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 49 publications
1
75
0
1
Order By: Relevance
“…We have found that over time, recurrent GBMs grow into deeper brain regions and the cortex recurs. Previous articles on GBM have not found reports of this phenomenon …”
Section: Discussionmentioning
confidence: 88%
“…We have found that over time, recurrent GBMs grow into deeper brain regions and the cortex recurs. Previous articles on GBM have not found reports of this phenomenon …”
Section: Discussionmentioning
confidence: 88%
“…To test this directly, we performed SMS on 14 GBM tumor and seven control biospecimens. As it is difficult to obtain fresh brain tissue samples from healthy individuals, we have followed the example of the TCGA Consortium and used epilepsy samples as a control for GBM (33)(34)(35). We analyzed the RNA sequencing data by testing expression of each annotated transcript in each individual GBM sample compared against all normal samples, rather than grouping all GBM samples together.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous report, transcriptomic data revealed that, for most cases, fragments from the same GBM sample could be classified into at least two molecular subgroups (4); needless to say, tumors consist of cells in different stages of transformation, resulting in both molecular and cellular heterogeneity. We recently assessed the proteomic profile of two different morphological regions from the same GBM sample derived from a formalin-fixed paraffin-embedded tissue (FFPE) (5) and found proteins exclusively identified in each region.…”
Section: Introductionmentioning
confidence: 99%